Development of elephant grass in response to irrigation with different levels of domestic sewage - Normand Vieira Fernandes, José; Suyane Marques Dantas, Mara; Moreira de Azevedo, Benito; Newdmar Vieira Fernandes, Carlos; Vieira Vasconcelos, Denise; Cristina da Silva Araújo, Isabel (Revista Ciência Agronômica, 2023)
The agricultural use of alternative water sources of inferior quality, such as reusing the water from domestic sewage, is seen as one way of increasing water availability, in addition to allowing the reuse of nutrients and organic matter, thereby helping to maintain the fertility and productivity of the soil. The aim of this study, therefore, was to evaluate growth, productivity and nutrition in elephant grass irrigated with different combinations of treated domestic effluent and well water. The experimental design was of randomised blocks, with six treatments and four replications, containing 10 plants in each plot. The treatments comprised five combinations of treated domestic effluent (TDE) and well water (WW): T1 (100% WW), T2 (25% TDE + 75% WW), T3 (50% TDE + 50% WW), T4 (75% TDE + 25% WW), T5 (100% TDE), and an additional treatment (T6) of 100% well water + a mineral fertiliser (NPK) recommended for elephant grass. The following variables were analysed: number of leaves, stem diameter, number of tillers, plant height, leaf area, fresh and dry weight of the leaves and stems, fresh and dry weight production, and the macronutrient content of the aerial part of the plant. The treatments applying the greatest levels of TDE had the closest mean values to those obtained under the conventional treatment, while the treatments applying 50% or more TDE were statistically equal by Tukey’s test (p < 0.05) to the conventional treatment.